Relationship between reproductive and creative components in the activities of musician and choreographer as leaders of folklore centers - Kovalska, O.V.; Reshetnikova, T.P.; Furdak, T.D. (Pedagogy of Higher and Secondary Education, 2009)
In this article, the interaction of art language in the creative work of musician: and dancers as leaden of the folklore structures different in the form of expression and ways of activity is considered.